Government Collaboration in Empowerment? A Collaborative Framework for the Government in Empowering Coastal Communities - Yusuf Fadli; Adie Dwiyanto Nurlukman (Journal of Government and Civil Society, 2018)
The pendulum of the development at the global level moves to the extent of collaborative work between government, society and third parties. Today, in Indonesia a collaboration model is also implemented with the aim of presenting long-standing welfare in coastal areas. The poverty that surrounds coastal communities is an anomaly in the midst of the abundance of wealth stored in the sea of Indonesia. The Regional Government of Tangerang Regency encourages to collaborate with external parties to resolve the troubles. This article tries to use the modified Triple-Helix model as an analytical framework, which is useful for knowing the role of actors involved in creating development innovation. This study uses qualitative methods to see and find out how political, social, and academic actors interact and integrate into overcoming public problems that arise from the perspective of collaborative governance. The findings of the study found, first, collaborative work is useful to improve governance, second, to provide opportunities for actors to find effective solutions, and thirdly, to increase trust between government and citizens. This article argues that the success of collaborative work depends on the synergy between actors and the extent to which each program can demonstrate its sustainability.